2011
DOI: 10.1111/j.1743-6109.2011.02472.x
|View full text |Cite
|
Sign up to set email alerts
|

New Insights from One Case of Female Ejaculation

Abstract: Introduction Although there are historical records showing its existence for over 2,000 years, the so-called female ejaculation is still a controversial phenomenon. A shared paradigm has been created that includes any fluid expulsion during sexual activities with the name of “female ejaculation.” Aim To demonstrate that the “real” female ejaculation and the “squirting or gushing” are two different phenomena. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 11 publications
1
59
1
1
Order By: Relevance
“…FE is an orgasmic expulsion of a smaller quantity of whitish fluid produced by the female prostate . Opinions regarding the quantity of expelled fluid vary from 1 mL to 30–50 mL . Following the work of E. Gräfenberg regarding the role of the urethra at sexual arousal , Addiego et al.…”
Section: Resultsmentioning
confidence: 99%
“…FE is an orgasmic expulsion of a smaller quantity of whitish fluid produced by the female prostate . Opinions regarding the quantity of expelled fluid vary from 1 mL to 30–50 mL . Following the work of E. Gräfenberg regarding the role of the urethra at sexual arousal , Addiego et al.…”
Section: Resultsmentioning
confidence: 99%
“…The term female ejaculation is often a shared paradigm that includes any fluid expelled during sexual activities. 51 Ejaculation orgasm, defined as a physiological response that occurs at the height of sexual arousal, manifests as either a 'real' female ejaculation (scanty, thick and whitish fluid from the Skene glands) or a squirting or gushing expulsion of a larger amount of diluted and changed urine. 48 Female ejaculation is thought to be an uncommon, physiological phenomenon that occurs only in some women, but can sometimes resemble orgasmic urinary incontinence.…”
Section: Coital Incontinencementioning
confidence: 99%
“…We concluded that the stable, or even improved, postoperative sexual function was, more likely than not, related to the elimination of “coital urinary incontinence” that many women with stress incontinence are, to varying degrees, distressed by during sexual activity 35, 36, 37. We emphasize the importance of distinguishing “coital urinary incontinence” from “female ejaculation and vaginal orgasm during sexual activity” as two distinctly different entities.…”
Section: Discussionmentioning
confidence: 85%